2016
DOI: 10.1007/s00216-016-0116-6
|View full text |Cite
|
Sign up to set email alerts
|

In ovo sexing of chicken eggs by fluorescence spectroscopy

Abstract: Culling of day-old male chicks in production of laying hen strains involves several millions of animals every year worldwide and is ethically controversial. In an attempt to provide an alternative, optical spectroscopy was investigated to determine nondestructively in ovo the sex of early embryos of the domestic chicken. The extraembryonic blood circulation system was accessed by producing a window in the egg shell and the flowing blood was illuminated with a near-infrared laser. The strong fluorescence and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 40 publications
5
34
0
5
Order By: Relevance
“…This result was consistent with the above explanation regarding increased blood production due to oestrogen synthesis receptors and enzyme production in females, which would result in higher blood levels and lower T575/T598 ratio. This findings agreed with what Galli et al (2017) reported, i.e. a steady-state increase in haemoglobin fluorescence in female embryos from d 4.5 to day 7.5.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result was consistent with the above explanation regarding increased blood production due to oestrogen synthesis receptors and enzyme production in females, which would result in higher blood levels and lower T575/T598 ratio. This findings agreed with what Galli et al (2017) reported, i.e. a steady-state increase in haemoglobin fluorescence in female embryos from d 4.5 to day 7.5.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, sexspecific development has been reported to occur from the onset of embryogenesis in domestic chickens with males developing faster than females during the first phase of incubation (∼30 h) due to over-expression of cellproliferation genes in males (Tagirov and Golovan 2015). This is in agreement with Galli et al (2017), who observed significantly higher haemoglobin fluorescence in male embryos at d 3.5, who used an in ovo fluorescence spectroscopic measurement of main vitelline vessels through an eggshell window.…”
Section: Discussionsupporting
confidence: 69%
“…Therefore, the source of this fluorescence and the possibility to exploit it for sex determination were further investigated [7]. First of all, it was observed that only the red blood cells display intense fluorescence, while all other embryonic and extraembryonic fluids and tissues give a Raman spectrum almost free from background.…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…Current options for the cessation of the practice include in-ovo-sexing (Galli et al 2017;Weissmann et al 2013) or the development of dual purpose breeds suitable for both egg and meat production. However, in surveys of Dutch citizens, there was little consensus about acceptable alternatives (Leenstra et al 2011;Gremmen et al 2018).…”
Section: Culling Day Old Malesmentioning
confidence: 99%